Psychological study of themes in Doyle's paddy Clarke ha ha ha and McCabe's the butcher boy through stream of consciousness - Abdul, Zanyar Kareem (2013)
Stream of consciousness is a narrative technique commonly seen as a product of modernism. It is a literary technique characterized by introspection, self-awareness and openness to the unconsciousness. The technique is a way of representing the whole mind of an individual, not just conscious thought. It is based on the psychological theory that human minds are made of many layers of awareness. The present study examines the various definitions of stream of consciousness technique as it is employed in Roddy Doyle’s Paddy Clarke HA HA HA and Patrick McCabe’s The Butcher Boy. Doyle and McCabe are prominent contemporary Irish writers, who seem to have a penchant for the technique of stream of consciousness in the style of Joyce and Woolf.Investigating stream of consciousness as a viable technique is another concern in the study in depicting the psyche and behaviour of the main characters Paddy Clarke in Paddy Clarke HA HA HA and Francie Brady in The Butcher Boy. This research also analyses the thematic issues and other literary devices that denotes the use of stream of consciousness which shows how the writers deal with the use of stream of consciousness in their writing. As the result of the study, thematic issues in the texts are found such as familial and societal issues, and development of the characters in relation to stream of consciousness. Literary devices such as shifting ideas, musicality, comic scenes,symbols, five senses and narration style are used to enhance the technique of stream of consciousness.